Caveolin Gene, a Possible Risk Factor for Metabolic Syndrome in Humans: A Systematic Review and Meta-Analysis - Mohadeseh Arefian; Sadegh Mazaheri-Tehrani; Maryam Yazdi; Roya Kelishadi (International Journal of Preventive Medicine)
Background: Studies show that caveolin genes are associated with metabolic disorders, so we aimed to systematically review the association between caveolin genes and metabolic syndrome in human studies. This systematic review is conducted based on the PRISMA 2020 checklist. Methods: A systematic literature search was done on electronic databases including Embase, Scopus, Medline (PubMed), and Web of Science until September 2023 and updated until June 2024. Human studies that were published in English were included without restricting other variables such as time, age, and gender. Results: At the first step, 10313 papers were found, and at the final step, nine studies were included in the systematic review, and four studies entered the quantitative analysis. The result showed that metabolic syndrome is significantly associated with minor alleles in the following genes: CAV-1 rs1997623 (OR = 1.44 (95% CI: 1.2, 1.86)), CAV-1 rs11773845, 22375–22375 del AC, and CAV-1 rs3807992. No significant association was found for CAV-1 rs926198 (OR = 1.61 (95% CI: 0.89-2.92)), and 22285 C>T. Caveolin mRNA level was increased in the cases of metabolic syndrome. CAV-1 rs1997623 A allele changes the transcription factor binding site to increase the attachment of EBF1. Conclusions: This results in the enhancement of promoter activity and further transcription of the caveolin-1 gene. In conclusion, individuals carrying minor alleles for the CAV-1 gene might have an increased risk for metabolic syndrome. With future studies focusing on the matter, this gene can be used as a screening tool for metabolic health to detect individuals with a higher genetic susceptibility to metabolic syndrome.